A review on international portfolio diversification: the Middle East and North African region - Mansourfar, Gholamreza; Ramadilli Mohd, Shamsher Mohamad; Hassan, Taufiq (Academic Journals, 2010)
Over the last three decades, international portfolio diversification has been the integral feature of global capital markets. Several potential benefits have been made investors to internationalize the portfolios. In this regards, emerging stock markets have been the subject of a large body of the international finance literature. It has also been more attractive for the practitioners in stock markets. This study provides an overview to the international portfolio diversification theory as well as a review on the evidence on this area. This review particularly focuses on the evidence from the Middle East and North African region; moreover, it suggests theoretical frameworks for further studies.